A finite strain thermodynamically-based constitutive framework coupling viscoelasticity and viscoplasticity with application to glassy polymers. (November 2017) - Gudimetla, Muralidhar Reddy; Doghri, Issam
Abstract: A large deformation viscoelastic-viscoplastic (VE-VP) constitutive framework is proposed for polymers. It is generic assuming isotropy and isothermal conditions and is developed with respect to the reference configuration by satisfying the Clausius-Duhem non-negative dissipation inequality. The Helmholtz free energy is the sum of four contributions: VE, VP, softening and hyperelastic re-hardening. The VE part has an integral form which takes into account the history of a rather non-classical VE strain measure. Various stress measures are computed. The flow rule and the VP response have general expressions in terms of the deviatoric and hydrostatic parts of the Mandel stress tensor. General Prony series are considered for the time-dependent VE moduli. Fully implicit time integration algorithms are presented. Application of the model is made to a glassy polymer -RTM6 Epoxy – where a strongly nonlinear finite strain response is observed in compression-dominated deformation mode. The results of numerical simulations are presented and compared to experimental data. Highlights: The proposed finite deformation model is thermodynamically-based which satisfies the Clausius-Duhem inequality. The VE part has an integral form taking into account the history of a non-classical VE strain measure. The flow rule and VP response have general expressions in terms of deviatoric and hydrostatic parts of Mandel stress tensor. Fully implicit time integration algorithms are presented. The model is validated by comparing the simulation results with the experimental data for glassy polymer-RTM6 epoxy-resin.